Tuning the mechanical properties of cellulose nanofibrils reinforced polyvinyl alcohol composites via altering the cellulose polymorphs. Issue 86 (2nd September 2016) - Miao, Xiaran; Tian, Feng; Lin, Jinyou; Li, Hui; Li, Xiuhong; Bian, Fenggang; Zhang, Xiangzhi
Abstract : Cellulose nanofibrils (CNF) with polymorphs of cellulose I and II are different in morphology, aspect ratio, density of functional groups and mechanical properties, which influence the reinforcement effect for polymer composites. Abstract : Cellulose nanofibrils (CNF) with polymorphs of cellulose I and II ( i.e. CNF-I and CNF-II) are different in morphology, aspect ratio, the density of functional groups and mechanical properties, which influence the reinforcement effect for polymer composites. In this work, two kinds of CNFs were fabricated from jute fibers by the TEMPO-mediated oxidation method followed by a mechanical disintegration. Highly transparent polyvinyl alcohol (PVA)/CNF composite films containing varying contents of CNF were obtained via evaporating solution blends of PVA and CNF. The mechanical and thermal properties of the PVA/CNF composites were extensively investigated. CNF-I led to a higher Young's modulus of the as-prepared composites than CNF-II did at the same content. The high density of functional groups on the surface of CNF-II enhances the interface interaction between PVA molecular chains and CNF, which result in a better toughness of the resultant composites. Meanwhile, both of CNF-I and CNF-II can improve the thermal stability and lower the degradation rate of PVA. This work provides an insight into the design of CNF reinforced composites with desired properties by altering the polymorphs of CNF.